2006
DOI: 10.1111/j.1542-4758.2006.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic changes of serum magnesium and their relation to hypotensive episodes in hemodialysis patients on different dialysates

Abstract: Magnesium is a crucial mineral, involved in many important physiological processes. Magnesium plays a role of maintaining myocardial electrical stability in hemodialysis patients. Intradialytic hypotension is a common complication of dialysis and it is more common with acetate dialysate. The significance of the intradialytic changes of magnesium and their relation to parathyroid hormone (PTH) level and calcium changes during dialysis, and their relation to hypotensive episodes during dialysis are interesting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 10 publications
1
35
0
1
Order By: Relevance
“…Over the long term, chronic hypomagnesemia can increase vascular calcification in hemodialysis patients [41,42]. In addition, there is concern about the potential hemodynamic and cardiovascular effects of acutely lowering the plasma magnesium level during hemodialysis [43,44]. Most importantly, serum magnesium has been recently reported to be a significant predictor of mortality in advanced renal disease patients [20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Over the long term, chronic hypomagnesemia can increase vascular calcification in hemodialysis patients [41,42]. In addition, there is concern about the potential hemodynamic and cardiovascular effects of acutely lowering the plasma magnesium level during hemodialysis [43,44]. Most importantly, serum magnesium has been recently reported to be a significant predictor of mortality in advanced renal disease patients [20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…These associations have been con fi rmed by more recent studies where the investigators reassured that intradialytic lowering in serum magnesium were signi fi cantly correlated with hypotension during the dialysis session [ 75,76 ] .…”
Section: Magnesium and Intradialytic Hemodynamic Stabilitymentioning
confidence: 82%
“…OALib Journal Recent results have indicated that low intradialytic serum magnesium level was associated with hypotensive episodes during HD [36] [41] [42]. Also, ESRD patients with low serum magnesium level were observed to have a higher and faster rate of vascular calcification [43] [44] [45].…”
Section: /14mentioning
confidence: 99%
“…Magnesium (Mg) is mainly excreted through the renal system and HD patients may have a normal, increased or decreased level of serum magnesium [36].…”
Section: Magnesium Disordersmentioning
confidence: 99%